A Case Report on the Progression of Myeloid Sarcoma to Form Multiple Metastatic Deposits without Developing Acute Myeloid Leukaemia - Sunita Kohli; Mark Lee; Scott Marshall (Case Reports in Hematology)
Introduction. Myeloid sarcomas (MS) are rare tumours occurring at extramedullary sites. They are usually associated with other haematology disorders such as acute myeloid leukaemia, myelodysplastic syndrome, and chronic myeloproliferative neoplasms. They frequently occur with a diagnosis of acute myeloid leukaemia (AML) or with relapse of preexisting disease. Patients with myeloid sarcomas without history or evidence of myeloid leukaemia typically progress to form AML. Case Presentation. A case report of a patient diagnosed with an isolated myeloid sarcoma that rarely did not transform to AML but instead spread to form multiple myeloid sarcomas throughout the body. Discussion. This case identifies the risk of metastatic spread of these tumours rather than the development of AML which is poorly documented in the literature, due to the rarity of cases, and may be significant in the investigation and management of isolated myeloid sarcomas. This case highlights the need for clinicians to consider repeat cross-sectional imaging to investigate unexplained clinical decline or symptoms, when there is no sign of AML progression and to consider radiotherapy treatment early.